Remarks on Homogeneous Al-Salam and Carlitz Polynomials - Jian-Ping Fang (Journal of Mathematics)
Several multilinear generating functions of the homogeneous Al-Salam and Carlitz polynomials are derived from q-operator. In addition, two interesting relationships of product of this kind of polynomials are obtained.